2017
DOI: 10.21577/0103-5053.20170175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Patients with Acute Lymphoblastic Leukemia: Experimental Evidence of the Efficacy of MDA as Cancer Biomarker in Young Patients

Abstract: Acute lymphoblastic leukemia (ALL) is a fatal disorder in most cases and is the most common cancer in young patients. ALL features an uncontrolled proliferation and maturation arrest of lymphoid progenitor cells (lymphoblast) in the bone marrow. An increase of reactive species production occurs in ALL with an involvement of oxidative stress (OS) and cellular damage. However, there is a lack of information about variations in young patients. The biomarker widely used to measure the OS is the main product of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…These data exhibit that the median levels of serum MDA are significantly higher in leukemia patients compared to the control group (P˂ 0.0357) showing in (Table 1 and Figure 1). This concurs with previous study that demonstrated the level of MDA in leukemia patients is significantly increased compared with control group [36][37][38][39]. These data are in disagreement with previous study that demonstrated the level of MDA in leukemia patients is significantly increased when compared to control group [40].…”
Section: Resultssupporting
confidence: 75%
“…These data exhibit that the median levels of serum MDA are significantly higher in leukemia patients compared to the control group (P˂ 0.0357) showing in (Table 1 and Figure 1). This concurs with previous study that demonstrated the level of MDA in leukemia patients is significantly increased compared with control group [36][37][38][39]. These data are in disagreement with previous study that demonstrated the level of MDA in leukemia patients is significantly increased when compared to control group [40].…”
Section: Resultssupporting
confidence: 75%
“…A study by Singh V, et al 17 reported significant decrease of MDA level between newly-diagnosed ALL patients and after the patients finished the chemotherapy. Increase of oxidative stress (increased MDA level) in ALL patients after ALL diagnosed positively correlated with increase in anti-apoptosis factors sFas-L and Bcl-2 which can initiate and promote ALL 13 .…”
Section: Discussionmentioning
confidence: 95%
“…Studies by Almeida MB, et al 13 , Al-Tonbary Y, et al 14 and Pujari KN, et al 15 showed that the MDA level was higher in ALL patients compared to normal subjects. This indicated that the increased lipid peroxides in ALL patients was the result of oxidative stress produced by free radicals 5 .…”
Section: Discussionmentioning
confidence: 95%
“…Terdapat 30 subjek dalam penelitian ini. Median kadar malondialdehid serum sebelum kemoterapi fase induksi adalah 77,63 (20,45-578,66) dan menurun menjadi 66,63 (22,3) setelah kemoterapi fase induksi, tetapi tidak signifikan secara statistik (p=0,60). Pada kelompok sesudah kemoterapi fase induksi, terdapat peningkatan status gizi baik pada 22 subjek (73,4%), sedangkan sebelum kemoterapi hanya terdapat 15 subjek (50%), tetapi tidak signifikan secara statistik (p=0,464).…”
unclassified
“…Oleh karena itu, penting untuk mengatasi dampak stres oksidatif selama kemoterapi pada pasien leukemia anak. 2,3 Kadar Malondialdehid meningkat saat awal kemoterapi sesuai dengan stres oksidatif, menjadikannya biomarker yang ideal. Pengukuran kadar ini akurat dengan berbagai metode dan stabil dalam sampel cairan tubuh yang diisolasi serta merupakan produk khusus peroksida lemak.…”
unclassified